1999
DOI: 10.1086/302609
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Genetic Analysis of 19 Wolfram Syndrome Kindreds Demonstrating a Wide Spectrum of Mutations in WFS1

Abstract: Wolfram syndrome is an autosomal recessive neurodegenerative disorder characterized by juvenile-onset diabetes mellitus and progressive optic atrophy. mtDNA deletions have been described, and a gene (WFS1) recently has been identified, on chromosome 4p16, encoding a predicted 890 amino acid transmembrane protein. Direct DNA sequencing was done to screen the entire coding region of the WFS1 gene in 30 patients from 19 British kindreds with Wolfram syndrome. DNA was also screened for structural rearrangements (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
172
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(185 citation statements)
references
References 18 publications
10
172
2
1
Order By: Relevance
“…To date, seven causative mutations have been identified within exon 5, of which five mutations [17][18][19]25,26 result in WFS, whereas two mutations 27,28 are associated with low-frequency sensorineural hearing loss. p.Asp211Asn is located in the N-terminal domain of the WFS1 protein.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, seven causative mutations have been identified within exon 5, of which five mutations [17][18][19]25,26 result in WFS, whereas two mutations 27,28 are associated with low-frequency sensorineural hearing loss. p.Asp211Asn is located in the N-terminal domain of the WFS1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Although many mutations have been identified in the WFS1 gene, most affected patients carry a mutation, either insertion, deletion, nonsense or missense, in exon 8, the largest exon of WFS1. 8,9,[16][17][18][19] The C-terminal hydrophilic part of the protein is the major site for missense mutations. Studies indicate that mutations affecting the translation of the last 10-15 amino acids result in a severe disease phenotype that confirms the functional importance of the C-terminus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…215 The region incorporates the Wolfram syndrome (phenotype includes insulin-dependent diabetes and optic atrophy) locus, WFS1. 216,217 Several mutations have been identified in WFS1, [216][217][218] and it has been suggested that variations in the WFS1 locus could play a minor role in the more common forms of diabetes mellitus. 216 Thus, these examples suggest that genes identified in oligogenic forms of diabetes may contribute to T1D susceptibility in the general population.…”
Section: Iddm2-the Insulin Gene (Ins) Regionmentioning
confidence: 99%
“…The observed consanguinity in about 25% of patients of different ethnicity [Gerbitz, 1999;Gomez-Zaera et al, 2001] is further evidence of a mendelian recessive mode of inheritance of the disorder. Actually, most WS patients carry loss-of-function mutations in the WFS1 gene (MIM# 606201), located at chromosome 4p16.1 and spanning a genomic region of 33.44 Kb [Hardy et al, 1999;Inoue et al, 1998]. Nevertheless, the recent identification of a second locus involved in WS (WFS2; MIM# 604928), mapped on chromosome 4q22-q24 [El-Shanti et al, 2000] has definitely confirmed the locus heterogeneity of this syndrome, hypothesized in the past [Collier et al, 1996].…”
Section: Introductionmentioning
confidence: 97%